Does Competence Determine Who Leads in a Dyadic Cooperative Task? A Study of Children with and without a Neurodevelopmental Disorder - Roy Vink; Fred Hasselman; Antonius H. N. Cillessen; Maarten L. Wijnants; Anna M. T. Bosman (Complexity)
Cooperative learning is an effective means for the acquisition of academic performance. It is an established fact that collaborating members should be operating in one another’s zone of proximal development to attain optimal performance. One variable that plays an as-yet unknown role in collaborative success is the leader-follower distinction. In the present study, leading and following behavior was determined by assessing rhythmical coordination of postural sway in typically developing children (n = 183) and children with a neurodevelopmental disorder (n = 106). Postural sway was measured using Nintendo Wii Balance Boards, and dyads performed a tangram task while standing on these balance boards, with the number of puzzles solved correctly serving as the measure of task performance. Irrespective of task performance, there was a consistent pattern of leading and following in typically developing dyads: the higher-ability child was in the lead. For children with a neurodevelopmental disorder, the pattern differed depending on task performance. While the patterns of low-performing dyads were comparable to those of typically developing children, high-performing dyads showed the opposite pattern; namely, the low-ability dyad member was in the lead. For interactions with children with a neurodevelopmental disorder and a low-level cognitive ability, it may be better to follow their lead, because it may result in better performance on their part.